Quasimonotone embedding of one-sided Lipschitz continuous functions - Herzog, Gerd (Mathematica Scandinavica, 2007)
We prove that one-sided Lipschitz continuous functions can be embedded into quasimonotone increasing functions, in a quite natural way. As a consequence of this result, quasimontonicity methods can be used to study initial and boundary value problems in Banach spaces if one-sided Lipschitz continuous functions are involved.